Enhanced natural convection in a U-shaped baffled cavity: Synergistic effects of magnetic fields and wall oscillations on Nano-encapsulated PCM - Ahmed M. Hassan (8893106) (2025)
Thermal management systems incorporating phase change materials have gained significant attention due to their high energy storage capacity and temperature control capabilities. Recent advances in nano-encapsulated phase change materials (NEPCMs) combined with magnetic field control offer promising solutions for enhanced heat transfer applications. However, the combined effects of mechanical oscillations and magnetic fields on NEPCM performance remain unexplored in complex geometries. This study investigates natural convection in a U-shaped baffled cavity filled with a nano-encapsulated phase change material (NEPCM) water mixture, featuring an oscillating bottom wall and subject to an inclined magnetic field. The finite element method is employed to solve the governing equations, with the Arbitrary Lagrangian-Eulerian approach used to handle the moving boundary. A comprehensive parametric study explores the effects of Rayleigh number (103–105), Stefan number (0.1–0.9), fusion temperature (0.1–0.9), nanoparticle volume fraction (0.01–0.04), oscillation amplitude (0.07–0.2), Hartmann number (0−20), and magnetic field angle (0°-90°) on heat transfer performance. Results show that the Rayleigh number has the most significant impact, increasing the time-averaged Nusselt number by 129.8 % as Ra rises from 103 to 105. Nanoparticle volume fraction also significantly enhances heat transfer, with a 58.9 % increase in Nusselt number as ϕ increases from 0.01 to 0.04. The optimal oscillation amplitude of 0.07 achieves a maximum Nusselt number of 1.4377, while larger amplitudes reduce heat transfer efficiency by up to 4.5 %. These findings provide valuable insights for optimizing thermal management systems utilizing NEPCM nanofluids in complex geometries with phase change processes. Other Information Published in: International Communications in Heat and Mass Transfer License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.icheatmasstransfer.2025.109051